Religion, Worldview, and Values in an International Class - Geir Hoaas (European Teacher Education Network, 2015)
Students attending the international course, "Multicultural Identity in a Global World" (MCI), in Oslo, come from many different European countries, some also from Asia, Africa, Latin-America or the USA. They meet and mingle daily and learn cultural codes and values from each-other, in classes of 24-32 students. During the course, they are challenged to present their own culture, with its values and norms, to their fellow-students, an eye-opener toward traits and values of their own culture. They are, furthermore, exposed to their own stereotypes and identity-markers, giving reason to think through their own attitudes toward peoples and cultures with different characteristics and values. Many of the students come from a secularized modern society in Europe, and in this encounter discover some deep structures in their own society, becoming more conscious of the religious roots and framework. Class-discussions go high under topics such as Cultural Identity and Cultural Awareness, Alternative Value Dimensions, Culture and Religion, Multicultural Competence, and Culture and Ethical Challenges. The students are also exposed to the multicultural environment of the city of Oslo, with more than 25% immigrant population, and schools and kindergartens in some areas of the town with as many as 80-90% of minority-background. Through an extensive questionnaire and interviews, to the classes of 2005-12, supplemented by impressions from class-discussions, we analyze the attitudes to Religion, Worldview and Values, as related to their home-culture, as well as the culture of the place of study.